2019
DOI: 10.1007/s12040-019-1086-9
|View full text |Cite
|
Sign up to set email alerts
|

C-equivalent correction factor for soil organic carbon inventory by wet oxidation, dry combustion and loss on ignition methods in Himalayan region

Abstract: Soil organic carbon (SOC) is an important parameter to study the carbon cycle as soil carbon stock inventory as well as to serve as prime indicator in assessing soil health and soil quality. The present study was attempted to investigate C-equivalent correction factor for SOC by Walkley-Black (wet oxidation) and loss on ignition (LOI) methods in relation to TOC analyzer (dry combustion) method. TOC analyzer method supposed to be the best method of total soil organic carbon estimation. Soil sample from 77 sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Second, a potential source of uncertainty may be the analytical method employed for analysis; for most samples (97 %), SOC content was analyzed using the wet-oxidation method, and a small number were analyzed by total combustion (CN elemental analyzer). Discrepancies in SOC results between combustion methods have identified wet combustion as a less reliable assessment method for SOC, as it tends to underestimate organic carbon at higher SOC contents (Kumar et al, 2019) and potentially overestimates it in highly reduced soils (Chatterjee et al, 2009). This issue has not been addressed in Chile to date.…”
Section: Data Harmonization Processing and Caveatsmentioning
confidence: 99%
“…Second, a potential source of uncertainty may be the analytical method employed for analysis; for most samples (97 %), SOC content was analyzed using the wet-oxidation method, and a small number were analyzed by total combustion (CN elemental analyzer). Discrepancies in SOC results between combustion methods have identified wet combustion as a less reliable assessment method for SOC, as it tends to underestimate organic carbon at higher SOC contents (Kumar et al, 2019) and potentially overestimates it in highly reduced soils (Chatterjee et al, 2009). This issue has not been addressed in Chile to date.…”
Section: Data Harmonization Processing and Caveatsmentioning
confidence: 99%
“…The difference in the analytical methods could be a source of uncertainty for future modelling initiatives which is not properly addressed in Chile on a national level. Discrepancies in the results of SOC analyses between combustion methods have identified wet combustion as an unreliable assessment method for SOC (Kumar et al, 2019). This is not yet properly addressed in Chile, as the recommended methods for SOC determination are still wet oxidation and loss on ignition, not mentioning dry combustion as a more accurate alternative (Sadzawka et al, 2006).…”
Section: Data Harmonization Processing and Caveatsmentioning
confidence: 99%
“…In our study, K showed a significant positive relationship with OC and SOM. This was reinforced by the finding of Gairola et al [52] and Kumar et al [70] and concluded that a layer of SOM enhances the K retention in the soils considerably. Greater K release is associated with oak individuals, which is the primary explanation for the greater K content in the soils of Moru oak and Kharsu oak forest [53].…”
Section: Influence Of Soil Nutrientsmentioning
confidence: 82%